Planning Practice between Ethics and the Power Game: Making and Applying an Ethical Code for Planning Agencies. (2nd March 2012) - Hoekveld, Gerard; Needham, Barrie
<x xml:space="preserve">Abstract</x> Abstract When considering how ethical considerations should be applied to the practice of spatial planning, most attention has been given to how individual spatial planners should do that. Our focus in this article is different: it is on the public agencies that carry out spatial planning. What ethical principles should they follow, both for determining the content of the planning policy and the procedures by which those principles are applied? We argue that it is possible to construct a 'domain ethics' specifically for spatial planning, a set of normative principles based on widely shared values and taking account of the peculiar features of spatial planning. Using four sources — some 'middle‐range' ethical principles, national law, international law, and the principles behind the idea of 'due process'— a domain ethics for spatial planning is put forward. In the 'power game' of planning practice, the public agency should adhere to these ethical principles. Ultimately, this is a task for the individual planner acting responsibly within the organization. We argue that planners should construct an ethical frame of reference, specifically adapted to every situation, which takes into account the nature and motivations of the other partners in that power game. That frame of reference should be established before the discussions and negotiations begin, and it should be used to influence them. Résumé Dans les études sur l'intégration de considérations déontologiques dans l'exercice de l'aménagement du territoire, on s'est attachéà la conduite à tenir par les aménageurs individuels. Cet article s'intéresse quant à lui aux organismes publics qui réalisent ce type d'aménagement. Quels principes éthiques devraient‐ils suivre pour décider à la fois la teneur des politiques d'aménagement et les procédures de mise en œuvre de ces principes? Il est possible d'élaborer une 'éthique du domaine' spécifique à l'aménagement du territoire, ensemble de principes normatifs fondés sur des valeurs partagées de manière générale et tenant compte des particularités de cette activité. Pour présenter cette déontologie, quatre sources sont exploitées: quelques principes éthiques 'de consensus', la législation nationale, le droit international, ainsi que les principes qui sous‐tendent la notion de régularité de la procédure (au sens de due process). Dans le 'jeu de pouvoir' liéà la pratique de l'aménagement, l'organisme public devrait respecter ces principes éthiques. Pour finir, il revient à chaque aménageur d'agir de manière responsable au sein de la structure concernée. Il conviendrait que les aménageurs élaborent un cadre de référence éthique, adaptéà chaque situation et tenant compte de la nature et des motivations des autres acteurs de ce jeu de pouvoir. Ce cadre de référence devrait être défini avant le début de toutes discussions ou négociations afin de pouvoir servir à les d'influencer.